Literasi Informasi Model The Big Six dalam Meningkatkan Mutu Pembelajaran di Madrasah Tsanawiyah - Anisah, Giati; Afifah, Siti Nur (CENDEKIA, 2023)
In the era of abundance information is manifested in various forms and can be accessed easily and quickly. The ability to select, evaluate, and use information is important to have. This study aims to describe the implementation of the big six models of information literacy in improving the quality of learning in Madrasah Tsanawiyah. This study uses a qualitative approach to the type of phenomenological research. Data collection was done by observation and interviews. Based on the results of the study, it was found that the implementation of learning using the big six model of information literacy can improve the quality of learning. The information literacy model of The big six includes six steps, namely problem formulation, strategy formulation, location and access determination, use, selection, information integration, and evaluation. Indicators that appear in students are proficiency in finding essential information, evaluating information, and using the information to solve problems. By mastering information literacy, critical, creative, innovative spirit and students' readiness to compete in the era of globalization is also developing. In addition, students will also be accustomed to making decisions, becoming independent human learners and easy to obtain new information